Neutrophil circadian rhythm is associated with different outcomes of acute kidney injury due to cholesterol crystal embolism - Shi, Chongxu; Zhao, Danyang; Lyubenov, Lyuben; Motrapu, Manga; Li, Na; Steiger, Stefanie; Mammadova-Bach, Elmina; Yang, Luying; Liu, Dong; Anders, Hans-Joachim (Frontiers in Cardiovascular Medicine, 2022)
Cholesterol crystal (CC) embolism can cause acute tissue infarction and ischemic necrosis via triggering diffuse thrombotic angiopathy occluding arterioles and arteries. Neutrophils contribute to crystal-induced immunothrombosis as well as to ischemic necrosis-related necroinflammation. We speculated that CC embolism-induced acute kidney injury (AKI) would be circadian rhythm-dependent and associated with cyclic differences in neutrophil function. Injection of CC into the left kidney induced thrombotic angiopathy progressing starting as early as 3h after CC injection followed by a progressive ischemic cortical necrosis and AKI at 24h. In C57BL/6J mice, circulating CD11b+Ly6G+ neutrophils were higher during the day phase (Zeitgeber time (ZT) 0-12) compared to the dark phase (ZT12-24). In the time frame of thrombus formation at ZT13, more neutrophils were recruited into the injured kidney 24h later compared to CC embolism at ZT5. This effect was associated with an increased circulating number of CXCR2+ neutrophils as well as an upregulated kidney adhesion molecule and chemokine expression. These findings were associated with a significant increase in kidney necrosis, and endothelial injury at ZT13. Thus, the time of day has an effect also on CC embolism-related AKI in association with the circadian rhythm of neutrophil recruitment.